2013
DOI: 10.1089/bfm.2012.0145
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding May Protect from Developing Attention-Deficit/Hyperactivity Disorder

Abstract: Children with ADHD were less likely to breastfeed at 3 months and 6 months of age than children in the two control groups. We speculate that breastfeeding may have a protective effect from developing ADHD later in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 19 publications
2
44
1
1
Order By: Relevance
“…118,119 A retrospective analysis of children 6-12 years of age who were diagnosed with ADHD relative to those without this disorder indicated breastfeeding may protect male and female offspring from developing this disorder. 120 Although such studies provide hints that breastfeeding may combat against developing complex neurological diseases, the findings may also be due to other confounding factors. These include genetics, environmental background, nutritional, overall health, socioeconomic, nutritional and metabolic status of both parents to list a few examples.…”
Section: Offspring Cancermentioning
confidence: 99%
“…118,119 A retrospective analysis of children 6-12 years of age who were diagnosed with ADHD relative to those without this disorder indicated breastfeeding may protect male and female offspring from developing this disorder. 120 Although such studies provide hints that breastfeeding may combat against developing complex neurological diseases, the findings may also be due to other confounding factors. These include genetics, environmental background, nutritional, overall health, socioeconomic, nutritional and metabolic status of both parents to list a few examples.…”
Section: Offspring Cancermentioning
confidence: 99%
“…20 Kadziela-Olech and Piotrowska-Jastrzebska, 2005;Mimouni-Bloch et al, 2013). On the other hand, children also exposed to PCBs postnatally via breastfeeding may show more severe deficits later in life in comparison to no-breastfed children (e.g., Verner et al, 2015a).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The literature to date has revealed that breastfeeding exposure and duration can have important implications for the neuropsychological and behavioral well-being of offspring [11,16,33,36,51,53]. Despite the increased attention given to the contribution of breastfeeding experiences during infancy to the subsequent functioning of offspring, most research focuses on child outcomes, with few studies exploring the effects of breastfeeding exposure and duration on neuropsychological and mental health outcomes during later life Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent line of research has indicated that breastfeeding can also protect against abnormal development of offspring across cognitive, psychological, social, and behavioral domains [11,16,33,36,51,53]. For example, research suggests that children who were breastfed for longer time periods tend to evince greater language ability [23], motor ability [23], and overall intelligence [52] relative to children who were never breastfed or who were breastfed for shorter durations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation